2007
DOI: 10.1139/w07-084
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and frequency of detection of fecalListeria monocytogenesshed by livestock, wildlife, and humans

Abstract: Listeria monocytogenes is a facultative intracellular pathogen that can be carried asymptomatically in various animals and can be shed in feces. We investigated the prevalence and characteristics of L. monocytogenes isolated from livestock, wildlife, and human potential sources of contamination in 2 areas in Ontario, Canada. From February 2003 to November 2005, a total of 268 fecal samples were collected from different animals. Listeria monocytogenes was isolated using selective enrichment, isolation, and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 39 publications
5
64
4
1
Order By: Relevance
“…Future studies may choose to measure the impact of wildlife and potential pathogen contamination by objective measures (e.g., the use of infrared cameras to detect wildlife in fields). Our study does provide quantitative data to support previous studies (2,12,19,25,32) that suggested that wildlife may be a source of pathogen contamination in fields. Furthermore, wildlife has also been suspected as the source of pathogen contamination in a number of produce-associated outbreaks (13,70,71).…”
Section: Field Practices Associated With Presence Of Pathogenssupporting
confidence: 85%
See 1 more Smart Citation
“…Future studies may choose to measure the impact of wildlife and potential pathogen contamination by objective measures (e.g., the use of infrared cameras to detect wildlife in fields). Our study does provide quantitative data to support previous studies (2,12,19,25,32) that suggested that wildlife may be a source of pathogen contamination in fields. Furthermore, wildlife has also been suspected as the source of pathogen contamination in a number of produce-associated outbreaks (13,70,71).…”
Section: Field Practices Associated With Presence Of Pathogenssupporting
confidence: 85%
“…Manas et al (30) determined that lettuce plants irrigated with nonpotable water had significantly higher rates of total coliforms and Salmonella contamination than lettuce irrigated with drinking water. A number of studies also have linked sporadic or repeated contamination events in produce fields to wildlife fecal deposits (21), with a variety of bacterial food-borne pathogens, including Salmonella and L. monocytogenes, regularly isolated from fecal samples collected from wildlife and domesticated animals (3,(31)(32)(33)(34)(35)(36). Salmonella can also survive in the soil for long periods of time (e.g., up to 230 days in one study [37]) when introduced by contaminated poultry or cow manure.…”
mentioning
confidence: 99%
“…Wildlife and birds can be carriers of L. monocytogenes (15,22,32). A potential role of feral animals in the maintenance and/or spreading of the pathogen on the study farm cannot be ruled out, as L. monocytogenes was previously isolated from one sample of feral animal feces collected from a feed bunker in June 2004 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Listeria monocytogenes has been isolated from many locations within dairy farms, including feces (32,39,40), animal drinking water (29,37,40), feeds or feed components (37,39), and milking equipment (29,30). A potential link between animal production systems and human listeriosis cases exists, as was suggested by previous studies that described the presence of L. monocytogenes ribotypes (39) or pulsed-field gel electrophoresis (PFGE) types (3,17) from farms that matched those observed for isolates from human listeriosis cases.…”
mentioning
confidence: 91%
“…In Mexico, Rodas-Suarez et al researched fish and seawater and found the 2.3% (1 of 68) of isolates were GM-resistant (Rodas-Suarez, 2006). In Canada, 31.8% (14/44) of isolates from the feces of dairy cow and isolates from the feces of wildlife animals were resistant to GM (Lyautey, 2007). These indicate that the GM-resistant isolates were mainly found from dairy products, clinical specimen and seafood.…”
Section: Discussionmentioning
confidence: 99%